Determinants of halal food purchasing decisions among undergraduates at UiTM Tapah - Zulkifli, Ilya Zulaikha; Jamian, Nurul Husna; Abdul Razak, Samsiah; Ahmad Ridzuan, Ahmad Nur Azam (UiTM Cawangan Perlis, 2025)
This study explores the factors influencing halal food purchasing decisions among undergraduates at Universiti Teknologi MARA Perak Branch, Tapah Campus. With the rising demand for halal products among Muslim consumers, understanding these drivers is vital for business and policy makers. The study examines the roles of religiosity, knowledge, perception, awareness, attitude, and branding and promotion in shaping student’s purchasing decisions. A quantitative research design was employed, utilizing a structured questionnaire distributed to conveniently selected 104 undergraduates from various programs. The study focused on six determinants such as Religiosity, Knowledge, Perception, Awareness, Attitude, and Brand and Promotion Influence. Meanwhile, the dependent variable is Halal Food Purchasing Decision. Multiple Linear Regression analysis was conducted using IBM SPSS version 23. The results revealed that three determinants such as religiosity, awareness, and attitude significantly influence halal food purchasing decisions as p-value less than 0.05. Specifically, religiosity (B = 0.177) and attitude (B = 0.332) showed a positive effect , while awareness had a negative effect (B = - 0.114). This study provides valuable insights for food manufacturers, marketers, and university administrators aiming to align strategies with young Muslim consumer’s needs. It also highlights the importance of educational initiatives in enhancing halal knowledge and awareness. Future research could expand the scope by conducting comparative studies across different campuses or student demographics.